Unveiling the Veil: Intangible Cultural Heritage and the Filipino College Students - Pastera, Robert John (Journal of Ethnic and Cultural Studies, 2024)
This study examined the current knowledge of Filipino college students on the Intangible Cultural Heritage (ICH) of the Philippines. The study included 75 college students during the academic year 2022-2023. Through a qualitative approach, the students submitted written essays anchored to the research questions. Thematic analysis was employed to analyze the qualitative data, adhering to the stages of open coding, axial coding, and selective coding. The analysis resulted in the surfacing of various themes which are the result of this study: (1) Exposure to art forms, (2) association with indigenous people, (3) essence of values and practices, (4) misunderstandings about ICH, and (5) safeguarding of ICH. Students who came from the provinces experienced ICH through their festivities and local cultures, which are annual celebrations of various communities. There were also students who observed their locality’s people, handicrafts, and even familial behaviors. The presence of various art forms, performances, and experiences with indigenous peoples, and local traditions, regardless of whether it is within their families or communities, and their own knowledge of recent social issues unveiled the opportunities for the students to be exposed to the concept of Intangible Cultural Heritage and safeguard it. The author proposed a recommendation to further study and formulate a probable teaching and learning approach for college students to be more exposed to the Intangible Cultural Heritage of the Philippines.